Production of Sophorolipid Biosurfactant by Insect Derived Novel Yeast Metschnikowia churdharensis f.a., sp. nov., and Its Antifungal Activity Against Plant and Human Pathogens - Kumari, Alka; Kumari, Sumeeta; Prasad, G. S.; Pinnaka, Anil Kumar (Frontiers in Microbiology, 2021)
Biosurfactants are potential biomolecules that have extensive utilization in cosmetics, medicines, bioremediation and processed foods. Yeast producing biosurfactants offer thermal resistance, antioxidant activity, and no risk of pathogenicity, illustrating their promising use in food formulations. The present study is aimed to assess potential biosurfactant screening from yeast and their inhibition against food spoilage fungi. A novel asexual ascomycetes yeast strain CIG-6AT producing biosurfactant, was isolated from the gut of stingless bee from Churdhar, HP, India. The phylogenetic analysis revealed that the strain CIG-6AT was closely related to Metschnikowia koreensis, showing 94.38% sequence similarity in the D1D2 region for which the name Metschnikowia churdharensis f.a., sp. nov. is proposed. The strain CIG-6AT was able to produce sophorolipid biosurfactant under optimum conditions. Sophorolipid biosurfactant from strain CIG-6AT effectively reduced the surface tension from 72.8 to 35 mN/m. Sophorolipid biosurfactant was characterized using TLC, FTIR, GC-MS and LC-MS techniques and was a mixture of both acidic and lactonic forms. Sophorolipid assessed promising activity against pathogenic fungi viz. Fusarium oxysporum (MTCC 9913), Fusarium solani (MTCC 350), and Colletotrichum gloeosporioides (MTCC 2190). The inhibitory effect of biosurfactant CIG-6AT against F. solani was studied and MIC was 49 µgm/ml, further confirmed through confocal laser scanning microscopy. We illustrated the antifungal activity of sophorolipid biosurfactant from Metschnikowia genus for the first time and suggested a novel antifungal compound against food spoilage and human fungal pathogen.